Efisiensi Pemasaran Karet Di Kabupaten Ogan Ilir Sumatera Selatan - Amalia, Azka; Rifin, Amzul; Rosiana, Nia (Forum Agribisnis, 2024)
ABSTRACT The rubber commodity in Ogan Ilir Regency plays an important role in increasing family income, but currently the income of rubber farmers is still relatively low because farmers are still traditional in their marketing, causing the prices received by farmers to be low. The aim of this research is to determine the existing rubber marketing channels in Ogan Ilir. Sampling was carried out randomly. 75 samples were used in this research, with a population of rubber farmers, namely 236 farmers in Tanjung Batu District and 254 in Payaraman District. Locations were chosen purposively based on the same considerations, namely the subdistricts and villages that produce the largest rubber production. Data collection uses cross-section data. Rubber marketing efficiency is analyzed using marketing margin, farmer's share, profit to cost ratio and the Data Envelopment Analysis (DEA) model. The research results show that rubber farmers in Ogan Ilir Regency use three marketing channel patterns. The most efficient marketing channel is marketing channel 1, namely (1) farmer-UPPB-factory and marketing channel 2 is an inefficient channel Keywords : marketing channel efficiency; rubber; UPPB.